PEMBENTUKAN KARAKTER SISWA DENGAN SISTEM BOARDING SCHOOL - Muhammad Solikhun (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The focus in this study was the implications of boarding school systemat Asri Islamic Boarding School on the character building of students atSMP Syubbanul Wathon Tegalrejo, especially regarding how todevelop and implement boarding school system to the charactereducation of the students at at SMP Syubbanul Wathon Tegalrejo. Thiswas a qualitative research, conducted at SMP Syubbanul WathonTegalrejo. The data collection techniques were observation, interview,and documentation. The data validity test was performed usingtriangulation of data sources. The data analysis used descriptivemethod. To conclude this research, boarding school model thatsupports character education of students is in the form of integratedlearning through teaching-learning method (dirasah wa ta’li), makinghabit of virtuous behavior (ta’dib), spiritual activities (riyadhah), aswell as giving a role model (uswah hasanah) by kyai/nyai and ustadz.In addition, the students’ activities are also monitored throughregulations. All these are to support an education system that couldresult in virtuous character building of the students, where they areexpected to be independent in many aspects of their daily lives.